The true identity of Neoneura bilinearis Selys, 1860, with the synonymy of N. gaida Rácenis, 1953, and the description of N. confundens sp. nov. (Odonata: Protoneuridae) - Wasscher, Marcel T.; van ’T Bosch, Johan G. (Zootaxa, 2013)
Study of rough notes and sketches made by D.C. Geijskes in 1972 and the recently found original drawings by E. de Selys Longchamps done in 1884 from the male syntype of Neoneura bilinearis Selys, 1860, shows the syntype male and female (now lost for several decades) of N. bilinearis refer to the same species later described as Neoneura gaida Rácenis, 1953. Therefore N. gaida is considered a junior synonym of N. bilinearis Selys, 1860. A neotype is chosen for the true N. bilinearis (neotype ♂, Suriname, Kabalebo, 15 viii 1965, in RMNH). N. bilinearis sensu Williamson (1917) is redescribed as Neoneura confundens sp. nov. (holotype ♂, Suriname, Jodensavanna, Koela-kreek, 13 ii 1946, in RMNH). N. confundens has a wide distribution in South America north of the Tropic of Capricorn, but it is lacking from the central and lower Amazon. It occurs in several color morphs and also varies in male appendage, genital ligula, and female pronotum morphology.